IMPLEMENTASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KELURAHAN KADIDI - Alfian Nur; Sapri Sapri; Ahmad Mannu (JIA: Jurnal Ilmiah Administrasi, 2021)
The purpose of this study is to determine the implementation of a complete systematic land registration program in Kadidi Village, Panca Rijang District, Sidenreng Rappang Regency and to determine what factors influence the implementation of a complete systematic land registration program in Kadidi Village, Panca Rijang District, Sidenreng Rappang Regency. The population of this research is 500 people, while the research sample is 83 people. The data collection technique used in this research is to use technique Literature Studies, Observation, Questionnaire, Interview. The collected data was then analyzed using a frequency table and using the SPSS application. The results of this study indicate that the implementation of the complete Systematic Land Registration Program in Kadidi Village, Panca Rijang District, Sidenreng Rappang Regency can be categorized as either with a percentage of 71.25% and the factors that affect the complete Systematic Land Registration Program in Kadidi Village, Panca Rijang District, Sidenreng Rappang Regency can categorized as good with a percentage of 75%.